Konfigurasi Bilah NACA 3612 Terhadap Performa Turbin Angin Sumbu Horizontal (TASH) - Wahyudi, Syahrul Nur; Al-Janan, Dony Hidayat (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2020)
To improve electrical energy better, the design and optimization of micro scale wind turbines has become a very important element in research. The aims are improving the ability to capture power and maximize energy production properly. The object of this study was horizontal axis wind turbine performance testing with the configuration of types and numbers of NACA 3612 blade variation in terms of output power (W), efficiency (Î·) and tip speed ratio (TSR). The tests carried out in the laboratory using a wind tunnel. There are 8 variations of wind speed, 1.41 m/s, 1.76 m/s, 2.51 m/s, 3.74 m/s, 4.81 m/s, 5.50 m/s, 5.71 m/s and 6.11 m/s. The results showed that the best power value was a taperless type with 2 blades of 0.846 watts with a maximum rotating speed of 876.3 rpm at 6.11 m/s wind speed. For the best efficiency value obtained at 3.74 m/s wind speed on the type of taper with a number of 4 blades of 2.9% at TSR 4.778. While the maximum TSR occurs in the type of taper with a number of 3 blades of 6.256 at 3.74 m/s wind speed by testing without using a prony brake.